Multifunctional Carbon‐Based Metal‐Free Electrocatalysts for Simultaneous Oxygen Reduction, Oxygen Evolution, and Hydrogen Evolution. Issue 9 (23rd December 2016) - Hu, Chuangang; Dai, Liming
Abstract : Rationally designed N, S co‐doped graphitic sheets with stereoscopic holes (SHG) act as effective tri‐functional catalysts for the oxygen reduction reaction, hydrogen evolution reaction, and oxygen evolution reaction, simultaneously. The multifunctional electrocatalytic activities originate from a synergistic effect of the N, S heteroatom doping and unique SHG architecture, which provide a large surface area and efficient pathways for electron and electrolyte/reactant transports.